(untitled) (International Research Journal of Management and Social Sciences, 2021)
Aim of this study is mediating effect of ambiance between food quality, brand awareness and customer satisfaction during COVID-19. The quantitative research approach was applied in this study, which utilized primary data and a sample of 222 business students who are consumers of KFC in Hyderabad. The data was collected through a questionnaire. The findings revealed that three partial mediation effect ambiance between food quality, brand awareness and customer satisfaction during COVID-19. Based on these findings it is important it for KFC top management should focus on ambiance in order to get more customer satisfaction during COVID-19. https://doi.org/10.5281/zenodo.10316525